Ecosystem-based fisheries management increases catch and carbon sequestration through recovery of exploited stocks: The western Baltic Sea case study - Scotti, Marco; Opitz, Silvia; MacNeil, Liam; Kreutle, Axel; Pusch, Christian; Froese, Rainer (Frontiers in Marine Science, 2022)
Legal requirement in Europe asks for Ecosystem-Based Fisheries Management (EBFM) in European seas, including consideration of trophic interactions and minimization of negative impacts of fishing on food webs and ecosystem functioning. This study presents the first mass-balanced ecosystem model focused on the western Baltic Sea (WBS). Results show that heavy fishing pressure exerted on the WBS has forced top predators such as harbour porpoise and cod to cover their dietary needs by shifting from forage fish to other prey or find food outside of the model area. The model was then developed to explore the dynamics of four future fishery scenarios: (1) business as usual (BAU), (2) maximum sustainable fishing (F = FMSY), (3) half of FMSY, and (4) EBFM with F = 0.5 FMSY for forage fish and F = 0.8 FMSY for other fish. Simulations show that BAU would perpetuate low catches from depleted stocks with a high risk of extinction for harbour porpoise. In contrast, the EBFM scenario would allow the recovery of harbour porpoise, forage fish and cod with increases in catch of herring and cod. EBFM promotes ecosystem resilience to eutrophication and ocean warming, and through the rebuilding of commercial stocks increases by more than three times carbon sequestration compared to BAU. The model provides an interrelated assessment of trophic guilds in the WBS, as required by European law to assess whether European seas are in good environmental status.